Performance Assessment of Some Operational Aspects of Revised National Tuberculosis Control Programme in Tuberculosis Unit, Nagpur, India - M. Chaudhary Sanjeev; S. Kubde Sanjay; P. Patil Sharad; Agrawal Sanjay (Journal of Preventive Medicine And Care, 2017)
Background : DOTS is the current international strategy for tuberculosis control endorsed by the World Health Organization and the International Union against Tuberculosis and Lung Diseases. Maharashtra achieved full coverage under RNTCP in October 2003. The programme was launched in Nagpur in the last quarter of 2002. Three years after its launch, it is the ideal time to assess the performance of programme to identify the operational challenges. Methods: This is a cross sectional study carried out in 'Sadar Tuberculosis Unit' of Nagpur Municipal Corporation with the objective to study performance of some aspects of RNTCP. Programme performance was explored through laboratory records review and non participant observations of all four designated microscopy centres. DOT centres were observed for accessibility, identifiability and the facilities provided to patients visiting for treatment. Performance of some operational aspects of RNTCP was assessed using standards, norms, procedures etc described in programme guidelines. Results: It was observed that the TB unit was manned with RNTCP- trained supervisory team. Three of four microscopy centres were established in multispecialty health facilities. Adequate space for sputum microscopy was available at two centres. Laboratory technician was available at three centres. Separate tables for smearing and staining were available at three centres. Sink, staining racks, spirit lamp, binocular microscope and drugs in patient - wise boxes were available in all four centres. Laboratory registers were completely and correctly filled in all centres. No false positive or false negative error was found in rereading of AFB smears. Conclusions: It is concluded that the performance of the programme at the unit is satisfactory. Still some aspects of the programme components need to be strengthened at microscopy centres for better performance of RNTCP.
Keywords: Programme Performance